2015
DOI: 10.1080/13548506.2014.997763
|View full text |Cite
|
Sign up to set email alerts
|

The acute psychobiological impact of the intensive care experience on relatives

Abstract: There is a growing awareness amongst critical care practitioners that the impact of intensive care medicine extends beyond the patient to include the psychological impact on close family members. Several studies have addressed the needs of relatives within the intensive care context but the psychobiological impact of the experience has largely been ignored. Such impact is important in respect to health and well-being of the relative, with potential to influence patient recovery. The current feasibility study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 24 publications
3
37
0
3
Order By: Relevance
“…Of note, family members of critically ill patients experienced cardiac anxiety during the first 3 days of the patient's hospitalization, and this anxiety should be taken into account by ICU doctors and nurses. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] To some extent, our results support previous findings 9-11 that family members of ICU patients experience acute stress, anxiety, depression, and stress-related disorders. Indeed, having a loved one close to death is a great burden and increases the psychological symptoms among the family members of patients in critical care units.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Of note, family members of critically ill patients experienced cardiac anxiety during the first 3 days of the patient's hospitalization, and this anxiety should be taken into account by ICU doctors and nurses. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] To some extent, our results support previous findings 9-11 that family members of ICU patients experience acute stress, anxiety, depression, and stress-related disorders. Indeed, having a loved one close to death is a great burden and increases the psychological symptoms among the family members of patients in critical care units.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, having a loved one close to death is a great burden and increases the psychological symptoms among the family members of patients in critical care units. [5][6][7][8][9][10][11][12][13][14][15] These psychological symptoms are explained in terms of severity of the patient's illness and the family members' fear of the patient's death. 10 However, our findings provide additional information on the biopsychological reactions among families of ICU patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kentish‐Barnes's study conducted in France contributed majority of the participants; it involved 242 family members from 22 ICUs across France. The results in this review were based on findings primarily from qualitative research designs with some results from mixed methods studies using semi‐structured interviews and questionnaire (see Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In line with that, Brereton concludes that a framework for the preparation of carers needs to be developed in order to enable caregivers to feel recognised as important in the caregiving role (Brereton & Nolan, 2000). Although researchers recognise that hospitalisation is a stressful event for the implicated (Eggenberger & Nelms, 2007;Turner-Cobb, Smith, Ramchandani, Begen, & Padkin, 2016;Vandall-Walker, Jensen, & Oberle, 2007), no recent studies and only a few were found that focused on the immediate emotional and social needs of relatives of stroke patients in hospital. Relatives of hospitalised stroke patients need information, counselling and access to health professionals according to Van der Smagt-Duijnstee, Hamers, and Abu-Saad (2000), and Brereton adds that during the early stages, the relatives needs for information were most apparent but also least well addressed (Brereton & Nolan, 2000); yet, Smagt-Duijnstee et al based their conclusion on a qualitative study raising questions like "Did you have contact with nurses on the ward?…”
Section: Introductionmentioning
confidence: 98%